2016
DOI: 10.5194/acp-16-5243-2016
|View full text |Cite
|
Sign up to set email alerts
|

Future vegetation–climate interactions in Eastern Siberia: an assessment of the competing effects of CO<sub>2</sub> and secondary organic aerosols

Abstract: Abstract. Disproportional warming in the northern high latitudes and large carbon stocks in boreal and (sub)arctic ecosystems have raised concerns as to whether substantial positive climate feedbacks from biogeochemical process responses should be expected. Such feedbacks occur when increasing temperatures lead, for example, to a net release of CO 2 or CH 4 . However, temperature-enhanced emissions of biogenic volatile organic compounds (BVOCs) have been shown to contribute to the growth of secondary organic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Clear-sky events not only cause the strongest deviations of the local urban climate, but also affect particle nucleation (Dada et al, 2017). Processes of turbulent mixing of atmospheric pollution in cold winter conditions remain a future focus of studies for the international research community (Arnold et al, 2016;Kim et al, 2017). Moreover, warmer climate conditions are Figure 8.…”
Section: Impacts Of a Strong Uhi In Arctic Citiesmentioning
confidence: 99%
“…Clear-sky events not only cause the strongest deviations of the local urban climate, but also affect particle nucleation (Dada et al, 2017). Processes of turbulent mixing of atmospheric pollution in cold winter conditions remain a future focus of studies for the international research community (Arnold et al, 2016;Kim et al, 2017). Moreover, warmer climate conditions are Figure 8.…”
Section: Impacts Of a Strong Uhi In Arctic Citiesmentioning
confidence: 99%
“…In MEGAN2.1, used in this study, CO 2 inhibition is included for isoprene. There are indications that the inhibition also affect monoterpenes and some studies include it also for monoterpenes (Arneth et al, 2016). Including CO 2 inhibition for monoterpenes could have reduced the difference is monoterpene emissions between the FB-ON and FB-OFF simulations and reduced the effect of the feedback.…”
Section: Limitations and Uncertaintiesmentioning
confidence: 99%
“…The response of isoprene emission to changing short-term environmental conditions, such as temperature and light, has been firmly established experimentally (Guenther et al, , 2012. Most of the regional to global studies that have considered BVOC emissions changes have concluded that non-LULC factors, due to climate change, are the largest factor affecting BVOC emissions in the long-term (100 years) periods (Arneth et al, 2016;Sanderson et al, 2003;Wiedinmyer et al, 2006;Xie et al, 2016). The changes are primarily associated with elevated temperature that increases isoprene emission, while elevated CO 2 can inhibit isoprene emission Heald et al, 2009;Tai et al, 2013;Tang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%